The Effect Of Work–Life Balance And Work Stress On Employee Performance At PT Perusahaan Gas Negara – Medan Branch Office - Swastika, Elsa; Waruwu , Ahmad Aswan (Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of work–life balance and work stress on employee performance at PT Perusahaan Gas Negara – Medan Branch Office. The object of this research is the employees of PT Perusahaan Gas Negara - Kantor Cabang Medan. The population and sample of this study consisted of 52 respondents. Data were processed using SPSS version 24. The data analysis included classical assumption tests and multiple linear regression analysis. The results show that the t-test for the work–life balance variable (X1) obtained a t-value of 2.938 > t-table 2.008 with a significance value of 0.005 < 0.05, meaning that work–life balance partially has a positive and significant effect on employee performance. The t-test result for the work stress variable (X2) obtained a t-value of -2.109 < t-table 2.008 with a significance value of 0.040 < 0.05, indicating that work stress partially has a negative and significant effect on employee performance. The F-test result shows that F-count 4.685 > F-table 3.187 with a significance value of 0.014 < 0.05. The coefficient of determination (R²) is 0.126 or 12.6%, indicating that the independent variables, work–life balance (X1) and work stress (X2), are able to explain the employee performance variable (Y) by 12.6%.